Laparoscopic assisted removal of multiple ingested magnetic foreign bodies in a child - Zahra Khalaf; Saeed Al Hindi; Rawaa Alsayegh (Journal of Pediatric Surgery Case Reports, 2021)
The phenomenon of magnet ingestion continues to pose a health risk. A key factor in understanding the risks associated is whether a single magnet or multiple magnets were ingested. When multiple magnets are involved, a magnetic field may be created across bowel loops risking obstruction, necrosis, fistula formation, volvulus, and ultimately peritonitis. Intervening in cases of magnet ingestion is case-specific. Factors such as the number of magnets, site of arrest, symptoms, and duration since the ingestion play a role in determining whether a conservative, medical, or surgical approach is indicated. We present a case of a 2-year-old child who presented with a one-day history of abdominal pain and vomiting. He was also refusing to eat or drink and had not passed bowel motions over the past day. On examination his abdomen was soft and non-tender. An abdominal x-ray revealed 7 pellet magnets in the small intestine. The magnet ingestion incident was unwitnessed. Laboratory investigations were within normal ranges. A laparoscopic assisted surgery was performed, and all magnets were successfully removed. There were no associated fistulae, perforations, or areas of necrosis.